Doppler Ultrasonography Of The Kidneys In Diabetic Patients - Ala Mohammed Abd Elgyoum Mohamed Ahmed; Abd Allah Mohammed Jaber; Amin A. E. Elzaki (Asian Journal of Medical Radiological Research, 2012)
This study was conducted with an aim to assess the effect of diabetes on the kidneys using ultrasonography, specifically to assess the vascularty ofkidneys by Doppler ultrasound in diabetic patients in Sudan. A total of forty seven samples of Sudanese diabetic patients between the mean ofages was 57.68 years were selected according to the positive evidence of diabetes. Features like patient shape, treatment taken, internalechogenicity, corticomedullary differentiation and renal artery indexes were employed.The examination of Doppler for 47patient showed that93.6% of patients had ordinary renal artery resistance and 6.4% had high resistance. The study also showed that there were relations between theaffection period of diabetic mellitus&changes happening in the kidneys such as renal failure 29.8%, pyelonephritis is 2.1%, renal artery stenosis6.4%. The study proved that diabetic patients were subject to multiple changes in abdominal organs that can be diagnosed by ultrasound, thissupports the use of ultrasound in diabetic treatment units.